2020
DOI: 10.1097/eja.0000000000001316
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged time to extubation after general anaesthesia is associated with early escalation of care

Abstract: BACKGROUND Prolonged time to extubation after general anaesthesia has been defined as a time from the end of surgery to airway extubation of at least 15 min. This occurrence can result in ineffective utilisation of operating rooms and delays in patient care. It is unknown if unanticipated delayed extubation is associated with escalation of care. OBJECTIVES To assess the frequency of ‘prolonged extubation’ after general anaesthesia and its association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…These data suggest the possibility that volatile anesthetics including desflurane may not exert bronchodilating effects or even may increase the respiratory resistance in patients with COPD or in smokers. Although the proportion of current smokers was similar between the two groups in this study, desflurane may not show bronchodilating effects or increase Several studies reported that age, BMI, and operation time were associated with prolonged extubation after general anesthesia including general anesthesia induced by volatile agents [13,14]. It has been shown that emergence and/or recovery from anesthesia are faster with desflurane than with sevoflurane, even in obese patients or elderly patients who are at higher risk for prolonged extubation [3,4,15].…”
Section: Discussionmentioning
confidence: 57%
“…These data suggest the possibility that volatile anesthetics including desflurane may not exert bronchodilating effects or even may increase the respiratory resistance in patients with COPD or in smokers. Although the proportion of current smokers was similar between the two groups in this study, desflurane may not show bronchodilating effects or increase Several studies reported that age, BMI, and operation time were associated with prolonged extubation after general anesthesia including general anesthesia induced by volatile agents [13,14]. It has been shown that emergence and/or recovery from anesthesia are faster with desflurane than with sevoflurane, even in obese patients or elderly patients who are at higher risk for prolonged extubation [3,4,15].…”
Section: Discussionmentioning
confidence: 57%
“…12–19 Thus, the current review was based on 19 articles obtained using Web of Science title and abstract search. 1–19…”
Section: Methodsmentioning
confidence: 99%
“…However, to date, no document has researched predictors for delayed extubation after thoracoscopic lung cancer surgery. Besides, many of the published factors associated with delayed extubation cannot be modified [ 18 ]. Further, no effective and well-performing model was established for predicting the possibility of delayed extubation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by reviewing a large number of medical records, this study aims to explore the incidence and potential predictors and to construct a nomogram to predict the decision to delayed extubation after this surgery. Moreover, considering the reported influence of timing of operation and attending handoff on delayed extubation in other surgical specialties [ 9 , 18 , 19 ], this study also attempts to investigate the interaction of the two factors on delayed extubation.…”
Section: Introductionmentioning
confidence: 99%